Vaccination options for recurrent urinary tract infection - Lionel M. Wallis, Daniel J. Wijaya, Luca T. Mayer (Open Journal of Physicians and Surgeons, 2024)
Recurrent urinary tract infections (UTIs) may be reduced through vaccination, which is in development against this medically troublesome, particularly for women, health problem. The whole life of an individual can be put at risk by the re-occurrence of urinary tract infections (UTIs), which will lead to overuse of antibiotics, and that creates a problem of resistance. There are several vaccine candidates that aim to stimulate the host immune system against uropathogenic Escherichia coli, the most common pathogen that causes the highest number of UTIs. A prominent candidate of Uro-Vaxom is a medicine, an oral immunostimulant meant to enhance the local immunity of the urinary tract and its effectiveness in reducing the incidence of UTIs. There are clinical studies that have shown that the outcome of the patients is better, and the patients have fewer UTIs. An additional investigational vaccine enters this field with the purpose of preventing bacterial binding events to the epithelium of the urinary tract by specific targeting of bacterial adhesion molecules. Whenever vaccines are used, there is often resort to lifestyle changes and preventive antibiotics. However, the development of effective vaccines could provide a long term approach towards relieving the need for antibiotics and their associated side effects.Continuous evaluation regarding the safety and efficacy of these vaccination options is necessary as they can change the treatment paradigm of recurrent UTI in certain populations